2020
DOI: 10.1017/s2045796020000694
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality and shortened life expectancy in people with major mental illnesses in Taiwan

Abstract: Aims Given the concerns of health inequality associated with mental illnesses, we aimed to reveal the extent of which general mortality and life expectancy at birth in people with schizophrenia, bipolar disorder and depressive disorder varied in the 2005 and 2010 nationally representative cohorts in Taiwan. Methods Two nationally representative samples of individuals with schizophrenia, bipolar disorder and depressive disorder were identified from Taiwan's national health insurance datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 21 publications
2
56
1
1
Order By: Relevance
“…Our finding on all-cause SMR for bipolar disorder is broadly consistent with the literature which reported 2–3 times greater overall mortality risk than the general population (Chang et al ., 2010 ; Crump et al ., 2013 ; Laursen et al ., 2013 ; Westman et al ., 2013 ), and is in line with a recent meta-analysis reporting all-cause summary SMR of 2.05 for bipolar disorder (Hayes et al ., 2015 ). In particular, our results are similar to the findings of Taiwan studies (the only recently published Asian studies in this respect), which revealed that all-cause SMR for bipolar disorder ranged from 2.39 to 2.65 (Pan et al ., 2017 , 2020 ). Of note, although we affirmed that bipolar disorder was associated with considerably shortened life expectancy after diagnosis, our observed magnitude of longevity gap is smaller than most previous estimates based on YLLs, ranging between 10 and 15 years shorter in lifespan than the general population (Chang et al ., 2011 ; Ajetunmobi et al ., 2013 ; Laursen et al ., 2013 ; Pan et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our finding on all-cause SMR for bipolar disorder is broadly consistent with the literature which reported 2–3 times greater overall mortality risk than the general population (Chang et al ., 2010 ; Crump et al ., 2013 ; Laursen et al ., 2013 ; Westman et al ., 2013 ), and is in line with a recent meta-analysis reporting all-cause summary SMR of 2.05 for bipolar disorder (Hayes et al ., 2015 ). In particular, our results are similar to the findings of Taiwan studies (the only recently published Asian studies in this respect), which revealed that all-cause SMR for bipolar disorder ranged from 2.39 to 2.65 (Pan et al ., 2017 , 2020 ). Of note, although we affirmed that bipolar disorder was associated with considerably shortened life expectancy after diagnosis, our observed magnitude of longevity gap is smaller than most previous estimates based on YLLs, ranging between 10 and 15 years shorter in lifespan than the general population (Chang et al ., 2011 ; Ajetunmobi et al ., 2013 ; Laursen et al ., 2013 ; Pan et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, our results are similar to the findings of Taiwan studies (the only recently published Asian studies in this respect), which revealed that all-cause SMR for bipolar disorder ranged from 2.39 to 2.65 (Pan et al ., 2017 , 2020 ). Of note, although we affirmed that bipolar disorder was associated with considerably shortened life expectancy after diagnosis, our observed magnitude of longevity gap is smaller than most previous estimates based on YLLs, ranging between 10 and 15 years shorter in lifespan than the general population (Chang et al ., 2011 ; Ajetunmobi et al ., 2013 ; Laursen et al ., 2013 ; Pan et al ., 2020 ). Recent research, however, indicates that LYL method yields more precise, though more conservative, estimates than prior measures of reduced life expectancy by incorporating variations in age of onset of the disorder into life expectancy calculation (Erlangsen et al ., 2017 ; Plana-Ripoll et al ., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations